Needed Epistemic Alliances: Gender, Sexuality, and Nation - González Fernández, Helena (Madrygal. Revista de Estudios Gallegos, 2025)
This article defends the alliance between gender and sexuality theories and discourses on nationhood, not as an accessory skills, but as a form of knowledge that addresses the national community’s constitutive singularities and provides critical knowledge. The aim is to offer some notes on issues to be considered to establish this alliance successfully. An overview is provided of the initiatives that launched gender and sexuality studies in Galicia since 1976. It demonstrates the theoretical power of studies based on the body, sex and sexuality, and some relevant contributions to reconceptualising not only dissident subjects, but also global issues, overcoming acosmia (worldlessness). It argues that feminist/queer skills is developed as a tripod of knowledge that comes from social movement, creation, and theory. It then questions the appropriateness of applying Harding’s theory of standpoint and the figure of the epistemically privileged subject. It provides a list of issues to be considered at the confluence of gender, sexuality, and nation, and explores the challenges posed by current debates on race and intersectionality. In summary, this article argues for the need to think about the national community from the singularity of bodies using the theoretical tools offered by critical gender/sexuality studies.
Keywords: Nation; Galician Culture; Feminist/Queer Epistemologies; Epistemic Privilege; Intersectionality